Intrathoracic sleeve gastrectomy migration with gastric volvulus treated with laparoscopic repair and conversion to gastric bypass - Alwatari, Yahya (J Surg Case Rep, 2020)
A 43 years old female with laparoscopic sleeve gastrectomy (SG) and an ‘anterior’ hiatal hernia repair 11 years ago, presented with 3 years history dysphagia and heartburn. Upper gastrointestinal barium showed an almost complete intrathoracic migration of the SG with a partial organoaxial volvulus. Upper endoscopy revealed a 10 cm hiatal hernia with grade B esophagitis. Laparoscopic revision surgery with reduction of the gastric sleeve, standard posterior hiatal hernia repair, resection of the narrowed remnant of the SG and conversion to a gastric bypass was performed. No postoperative complications occurred. The patient is asymptomatic at 2 years of follow-up. We present the technical standards for the management and discuss the suspected pathophysiology of this rare but challenging condition.